The fire break in Bialowieza national park as a refuge of the segetal flora - Bomanowska, A.; Adamowski, W. (Український ботанічний журнал, 2013)
Taking into account the extensive scale of farmland
abandonment in the area of the Bialowieza Primeval Forest, the
authors decided to investigate the flora of the fire break in Bialowieza National Park as potential refuge for segetal flora. One hundred and thirty-six plant taxa have been found to occur on the fire
break, including 101 common to the segetal flora of the Biaіowiea
Clearing. The most widespread species are Anthemis arvensis,
Juncus bufonius and Scleranthus annuus; the most interesting are
Peplis portula and Ranunculus sardous, formerly growing in wet
furrows. Our results show that the ploughed fire break could be a
refuge for segetal flora. Враховуючи широкі масштаби занедбаних сільськогосподарських угідь, автори досліджували флору вогнезахисних смуг Біловезького національного парку як потенційного осередку сегетальної флори. Виявлено 136 таксонів судинних рослин, у т.ч. 101 спільний для сегетальної флори вирубок Біловежі. Найбільш поширеними видами є Anthemis arvensis, Juncus bufonius і Scleranthus аnnuus, найбільш цікавими — Peplis portula і Ranunculus sardous, які раніше росли у вологих борознах. Наші результати вказують, що зорані вогнезахисні смуги можуть бути рефугіумом сегетальної флори. Учитывая широкие масштабы запущенных сельськохозяйственных угодий, авторы исследовали флору огнезащитных полос в Беловежском национальном парке как потенциальный рефугиум сегетальной флоры. Выявлено 136 таксонов сосудистых растений, в т.ч. 101 общий для сегетальной флоры вырубок Беловежи. Наиболее распространенными видами являются Anthemis arvensis, Juncus bufonius и Scleranthus аnnuus, наиболее интересными — Peplis portula і Ranunculus sardous, которые раньше произрастали во влажных бороздах. Наши результаты указывают на то, что вспаханные огнезащитные полосы могут служить рефугиумом сегетальной флоры.